Lōkakavi Vēmana yōgi : jīvitamu, padyamañjari, praśaṃsalu - Kothandarama Reddi, Marupooru, 1902- (Kōdaṇḍarāmareḍḍi, 1983)
On the life of Vēmana, 17th century Telugu poet and philosopher; includes a selection of his verses.